Qualidade fisiológica de sementes de trigo em função do suprimento combinado de nitrogênio e enxofre - Zimmer, Thais Ongaratto de Camargo (2023)
Wheat is an important item in the basic feeding habits of Brazilians and, thus, alternatives for increasing yield in this crop are being explored. To reach new yield levels, solutions that incorporate other nutrients besides the traditional fertilization with nitrogen, phosphate and potassium sources have been tested with promising results. However, the benefits of using comprehensive solutions might bring additional advantages, besides the increases in yield. Therefore, the objective of this study was to evaluate the effect of doses of fertilization with nitrogen and sulfur in the physiological quality of wheat seeds. The experiment was carried out using Random Complete Blocks with four statistical repetitions for each treatment. Wheat seeds were produced in the 2021 and 2022 growing seasons at the Palma Agricultural Center at the Federal University of Pelotas using two fertilizers as nitrogen sources (Urea and Yaravera) and the doses of 0, 40, 80 e 160 kg of N per ha. The variables evaluated were the hectoliter weight, yield, germination, and seed vigor in the tests of seedling length (root, shoot and total), seedling dry matter (root, shoot and total), accelerated aging, cold, first count of germination and electrical conductivity. Data were evaluated for the presumptions of the analysis of variance using the Shapiro-Wilk test and the analysis of variance using the F test in the 5% probability level. For simple effects of dose, the regression analysis was performed and for the simple effect of source the comparison was performed using the t test at the 5% probability level. For interactions among factors the most representative polynomial was calculated for each source. The results demonstrated that nitrogen fertilization increased yield, hectoliter weight and wheat seed vigor in the tests of first count of germination, seedling length and dry matter, accelerated aging and electrical conductivity. Additionally, the results also indicate that modern fertilizers that also contain the nutrient sulfur might potentialize this beneficial effect in seed vigor with greater increases in variables such as root and total seedling length, seedling shoot and total dry matter, accelerated aging and in the decrease of the values observed in the electrical conductivity test.